Prawny i katechetyczny wymiar "Drogi Neokatechumenalnej" - Domaszk, Arkadiusz (Prawo Kanoniczne, 2009)
The catechistic instruction fulfils an important part in the mission of the Church, among other things that serves to the initiation to the Christian and stable its education into the faith. This thought of the Church undertook the Neocatechumenal Way which came to life in the sixties of the XX Century and is still present in many countries and dioceses. To the development of neocatechumenal communities accompanied the interest of the Magisterium of the Church. The meaning Neocatechumenal Way is especially important on the catechistic field. The educated model of the formation, links back to ancient catechumenat, is useful and fruitful in the gradual and general Christian education and in the evangelization of the present world. The Statutes Neocatechumenal Way, confirmed finally in 2008, possesses also a legal importance. The practice this Way became consequently recognized by the Church. Also an important event was the acknowledgement of the public legal personality of the Neocatechumenal Way. From here the Way enrolls into the realization of the church mission. A consequence of these events is among other things, the adaptation of the liturgy performed in neocatechumenal communities to liturgical rules. Current attempts of defining – what is Neocatechumenal Way in the Church, do not give an univocal answer. This is not one of the church associations, nor other typical ecclesiastical structure. It seems that this is the completely new church formula (in the process of the formation itself) which couldn’t be attributed to until now that is recognized. Christians’ charisma and the attendance of the Saint Spirit produce in the church new practical forms, and simultaneously legal. So understood plurality of ways and the wealth of the Christian life existed in the history. The church recognized the new charisma, also at present and the Magisterium of the Catholic Church accompanies the Neocatechumenal Way.